UNDERSTANDING ADAT LAW NORMS RESISTANCE TO THE PROHIBITION OF PASUNG: LEGAL AND SOCIAL CHALLENGES IN KAPANEWON GIRISUBO, GUNUNG KIDUL - Rimawati Rimawati (Cepalo)
The practice of pasung (physical restraint/shackling) of individuals with mental disorders remains prevalent in rural Indonesia, particularly in Kapanewon Girisubo, Gunungkidul, despite its prohibition under Law No. 17 of 2023 on Health and Yogyakarta Governor Regulation No. 81 of 2014. This persistence is driven by entrenched adat (customary) norms, social stigma, economic limitations, and inadequate mental health infrastructure. This study analyzes the interaction between adat law and national legal frameworks in regulating the prohibition of pasung, using a socio-legal approach to explore the dynamics of legal pluralism in mental health governance. Findings show that while national law prohibits pasung, local communities often legitimize it through traditional beliefs and in response to the absence of accessible care. The study concludes that bridging the gap between adat and state law requires culturally sensitive legal strategies and stronger government commitment to expanding mental health services.